Aktivitas Makan Monyet Ekor Panjang (Macaca fascicularis) di Bumi Perkemahan Pramuka, Cibubur, Jakarta - Farida, Hilda; Perwitasari-Farajallah, Dyah; Tjitrosoedirdjo, Sri Sudarmiyati (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Long-tailed macaque (Macaca fascicularis) is one of the non human primates which is widely distributed. Long-tailed macaques live in a group consisted of multimales and multifemales. The group size was determined by predator, food resources, and foraging efficiency. Bumi Perkemahan Pramuka Cibubur is a habitat for long-tailed macaques. This place is a camp area and tourism site, which is predominated by akasia (Acacia auriculiformis). This research is aimed to study feeding activity of long-tailed macaque in Bumi Perkemahan Pramuka, Cibubur, Jakarta. Methods used in this research were habituation, census, ad libitum sampling, focal animal sampling, and scan sampling. The identification of food items was carried out by means of direct observation, interview, specimen collection, and identification of plant species. Feeding activities of long-tailed macaques constituted 9.01% of the total daily activities. Food consumed consists of natural and non natural food. Natural food items were leaf buds of awi tali (Gigantochloa apus) 34.76%, jukut pait (Axonopus compressus) 22.61%, and fig (Ficus benjamina) 7.15%, respectively. Furthermore, non natural food items were food leftovers of visitors 29.00% and peanuts 15.52%, respectively. In general, natural food (74.02%) was consumed more frequent than those of non natural food (25.98%).